Field observations of the Japanese Arctic Glaciological Expeditions in Svalbard from 1993 to 1995 (report) - Kamiyama, Kokichi; Motoyama, Hideaki; Watanabe, Okitsugu (2001)
P(論文) The Japanese glaciological expedition continued its research in Svalbard from 1993 to 1995. The main interest is to clarify fluctuations of present and past Arctic environments. Ice coring provides past, and snow surveys present, climatic information. The corings were carried out on the central glacier in 1993,on small glacier near the seashore in 1994 and on a large glacier in the northernmost island in 1995. The snow survey was carried out mainly in 1994. departmental bulletin paper